Prevalence of Helicobacter pylori infection and its associated factors in patients with COVID-19 - Nikpour, Shahriar; Gachkar, Latif; Rezaei, Reza; Salehi, Mohammad; Futuhi, Farzaneh; Sabeti, Shahram; Shabani, Minoosh; Erfanifar, Azam (Novelty in Biomedicine, 2022)
Background: The severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) attaches to the angiotensin-converting enzyme-2 (ACE-2) receptors for penetrating cells. Because these receptors are extensively distributed in the intestine, coronavirus disease 2019 (COVID-19) may cause gastrointestinal (GI) symptoms. Helicobacter pylori (H. pylori) is known to increase the expression of ACE-2 receptors in the GI tract. This study aimed to investigate the prevalence of H. pylori infection and its associated factors in patients with COVID-19. Materials and Methods: This cross-sectional study was conducted from February to December 2021. A total of 215 patients who had been diagnosed with COVID-19 infections using a real-time PCR test or a CT scan were included in the study. The enzyme-linked immunosorbent assay (ELISA) test on serum samples was used to evaluate the presence of H. pylori. Results: All 215 positive patients for COVID-19 with a mean age of 59.72±17.23 were evaluated. Among them, 153 patients (71.2%) were H. pylori-positive. Moreover, H. pylori+/ COVID-19+ group showed higher mean age than H. pylori-/ COVID-19+ patients. However, there was no significant difference between the two groups of patients regarding their medical background, drug history, BMI, and disease severity. The prognosis of the patients was severely worse in the H. pylori+/ COVID-19+ than in H. pylori-/ COVID-19+ patients. Conclusion: Our study adds to the previous findings and provides evidence regarding the high prevalence of H. pylori in COVID-19 patients. These investigations could help us elucidate the relationship between H. pylori and respiratory system findings and better understand COVID-19.